Ethics and Benefits of Lasisma in Islamic Economics Perspective : Etika dan Manfaat Lasisma dalam Perspektif Ekonomi Islam - Rekhan Abdillah; Nawal Ika Susanti (Academia Open, 2025)
General Background: Community-based financial services play a pivotal role in addressing financial exclusion and fostering equitable development, particularly in regions with limited access to conventional banking. Specific Background: Within the Islamic economics framework, Layanan Simpan Pinjam Jamaah (Lasisma) at BMT NU Genteng embodies ethical finance through the Qard Hasan contract—an interest-free loan aligned with Sharia principles. Knowledge Gap: However, empirical studies on the ethical dimensions and socio-economic outcomes of such models remain scarce. Aims: This study aims to examine the ethical practices, economic benefits, and community impacts of Lasisma in promoting financial inclusion and social justice. Results: Using interviews and document analysis, the research finds that Lasisma fosters transparency, fairness, and mutual benefit while enhancing community solidarity and empowering small businesses. Novelty: The study offers a unique insight into how a localized, faith-based financial initiative operationalizes Islamic economic values in practice, particularly through collateral-free, ethical financing. Implications: The findings contribute to the discourse on sustainable economic development by illustrating how community-rooted Islamic financial services can serve as viable alternatives to conventional microfinance, aligning with both ethical mandates and socio-economic empowerment goals. Highlights: Promotes ethical, interest-free financing based on Islamic principles. Strengthens community solidarity and financial accessibility. Supports local businesses through collateral-free microloans. Keywords: Qard Hasan, Islamic Economics, Community Based Services, Social Justice, Economic Empowerment.